A conceptual framework of challenges and solutions for managing global software maintenance. Issue 10 (21st June 2015) - Ulziit, Bayarbuyan; Warraich, Zeeshan Akhtar; Gencel, Cigdem; Petersen, Kai
Abstract Context Software maintenance process in globally distributed settings brings significant management challenges to software organizations. Objectives Investigate the factors specific to managing software maintenance process in globally distributed settings and best practices in software organizations. Method A systematic literature review and interviews with industry practitioners were conducted. For analysis and synthesis, the grounded theory method was used. Results We identified a number of management challenges and mitigation strategies and then classified them under people, process, product, and technology factors. Overall, a structure of challenges and solutions, the conceptual framework, has been developed that may be used to understand and classify global maintenance challenges. Conclusions Distributed software maintenance process has specific management challenges in relation to process, people, product, and technology. Therefore, companies performing maintenance in distributed settings should consider these factors, which are not present in the general global software development literature, although many lessons apply to both. Copyright © 2015 John Wiley & Sons, Ltd.